Market reaction to bank liquidity regulation - Bruno, Brunella; Onali, Enrico; Schaeck, Klaus (Cambridge University Press, 2018)
We measure market reactions to announcements concerning liquidity regulation, a key innovation in the Basel framework. Our initial results show that liquidity regulation attracts negative abnormal returns. However, the price responses are less pronounced when coinciding announcements concerning capital regulation are backed out, suggesting that markets do not consider liquidity regulation to be binding. Bank- and country-specific characteristics also matter. Liquid balance sheets and high charter values increase abnormal returns whereas smaller long-term funding mismatches reduce abnormal returns. Banks located in countries with large government debt and tight interbank conditions or with prior domestic liquidity regulation display lower abnormal returns.